2015
DOI: 10.4103/0259-1162.150681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of oral flupirtine and oral diclofenac sodium for analgesia and adverse effects in elective abdominal surgeries

Abstract: Background:Flupirtine is a centrally-acting, nonopioid analgesic that interacts with N-methyl-D-aspartate receptors.Aim:The present study was designed to compare analgesic efficacy and adverse effects of orally administered flupirtine and diclofenac sodium for postoperative pain relief.Settings and Design:In a prospective, randomized double-blind study, 100 patients of American Society of Anesthesiologist grade I and II in the age group of 18–65 years of either sex undergoing elective abdominal surgeries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…The reduction in pain was significant at all points of time following 48 hours treatment compared to baseline in both the groups. This observation partly correlates with the findings of another study, 10 indicating that though both the study drugs have a slight delay in onset, they have a longer duration of analgesia. Flupirtine used as preemptive analgesic in laparoscopic cholecystectomy surgery had provided adequate pain relief postoperatively in a study conducted by Yadav et al 11 and in postabdominal hysterectomy study conducted by Thapa et al 12 These studies indicate that preemptive use of flupirtine could provide immediate postoperative pain relief; hence, administering this drug preemptively followed by postoperative dosing may be a better method for postoperative analgesia in orthopedic surgeries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The reduction in pain was significant at all points of time following 48 hours treatment compared to baseline in both the groups. This observation partly correlates with the findings of another study, 10 indicating that though both the study drugs have a slight delay in onset, they have a longer duration of analgesia. Flupirtine used as preemptive analgesic in laparoscopic cholecystectomy surgery had provided adequate pain relief postoperatively in a study conducted by Yadav et al 11 and in postabdominal hysterectomy study conducted by Thapa et al 12 These studies indicate that preemptive use of flupirtine could provide immediate postoperative pain relief; hence, administering this drug preemptively followed by postoperative dosing may be a better method for postoperative analgesia in orthopedic surgeries.…”
Section: Discussionsupporting
confidence: 89%
“…Similar studies by Attri et al and Ahuja et al, which compared flupirtine with other NSAIDs, also revealed no significant difference between the medications in reducing postoperative pain. 5 , 10 , 14 These studies were conducted on patients undergoing gynecological and other abdominal surgeries unlike the current study which was carried out in limb surgeries. The extensiveness and increased sensitivity of osteoid tissues tend to result in severe postoperative pain following surgeries involving the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Attri et al . [ 28 ] in a study on elective abdominal surgeries found that hemodynamics in flupirtine- and diclofenac-treated groups was quite comparable. However, surprisingly, in our study, mean dose of esmolol and the number of patients receiving the same were significantly high in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be assumed that there is a high number of unreported cases. In a prospective, randomized clinical trial regarding postoperative administration of Diclofenac, 58% of patients reported impaired taste sensation (Attri et al, 2015). Therefore, it seems likely that diclofenac affects taste sensation due to the inhibition of hP2X2/3R.…”
Section: Selectivity Profiling Of Diclofenac At P2x Receptors and Rel...mentioning
confidence: 99%